Urologic malignancies in kidney transplantation. Issue 1 (1st December 2017) - Hickman, Laura A.; Sawinski, Deirdre; Guzzo, Thomas; Locke, Jayme E.
Abstract : With advances in immunosuppression, graft and patient outcomes after kidney transplantation have improved considerably. As a result, long‐term complications of transplantation, such as urologic malignancies, have become increasingly important. Kidney transplant recipients, for example, have a 7‐fold risk of renal cell carcinoma (RCC) and 3‐fold risk of urothelial carcinoma (UC) compared with the general population. While extrapolation of data from the general population suggest that routine cancer screening in transplant recipients would allow for earlier diagnosis and management of these potentially lethal malignancies, currently there is no consensus for posttransplantation RCC or UC screening as supporting data are limited. Further understanding of risk factors, presentation, optimal management of, and screening for urologic malignancies in kidney transplant patients is warranted, and as such, this review will focus on the incidence, surveillance, and treatment of urologic malignancies in kidney transplant recipients. Abstract : The authors provide a comprehensive review of risk factors, presentation, optimal management of, and screening for urologic malignancies in kidney transplantation.